Pengaruh E-Service Quality, Harga, dan Promosi terhadap Kepuasan Pelanggan Transportasi Online - Damayanti, Biyanda Dwi; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Knowing the effect of e-service quality, price, and promotion on Gojek customer satisfaction is the aim of this research. This research was conducted in Denpasar City. The population in this study is all the people of Denpasar City who use Gojek services throughout 2022 which are infinitive. The sample size was determined as many as 140 people with judicial sampling. This study used a questionnaire with a Likert scale with five answer choices. Multiple linear regression was established as an analytical technique for testing hypotheses. The results of the analysis prove that customer satisfaction of 81.6 percent is caused by a combination of e-service quality, price and promotions. The results of the partial significance analysis prove that each of e-service quality, price, and promotion has a positive and significant effect on customer satisfaction.